CHOLINE TRANSPORTER-LIKE1 is required for sieve plate development to mediate long-distance cell-to-cell communication - Dettmer, Jan; Ursache, Robertas; Campilho, Ana; Miyashima, Shunsuke; Belevich, Ilya; O'Regan, Seana; Mullendore, Daniel Leroy; Yadav, Shri Ram; Lanz, Christa; Beverina, Luca; Papagni, Antonio; Schneeberger, Korbinian; et al. (Nature Communications, 2014)
Phloem, a plant tissue responsible for long-distance molecular transport, harbours specific junctions, sieve areas, between the conducting cells. To date, little is known about the molecular framework related to the biogenesis of these sieve areas. Here we identify mutations at the CHER1/AtCTL1 locus of Arabidopsis thaliana. The mutations cause several phenotypic abnormalities, including reduced pore density and altered pore structure in the sieve areas associated with impaired phloem function. CHER1 encodes a member of a poorly characterized choline transporter-like protein family in plants and animals. We show that CHER1 facilitates choline transport, localizes to the trans-Golgi network, and during cytokinesis is associated with the phragmoplast. Consistent with its function in the elaboration of the sieve areas, CHER1 has a sustained, polar localization in the forming sieve plates. Our results indicate that the regulation of choline levels is crucial for phloem development and conductivity in plants.